IMPLEMENTATION OF GUIDANCE AND COUNSELING SERVICES IN OVERCOMING STUDENTS’ LEARNING AND PERSONAL PROBLEMS AT SMP UNIVERSAL SCHOOL DENPASAR - Opirman Waruwu (Counseling For All : Jurnal Bimbingan dan Konseling, 2026)
This study aims to examine the implementation of guidance and counseling services and their role in addressing students’ academic and personal problems at SMP Universal School Denpasar. This research used a qualitative descriptive approach, with data collected through observation, interviews, and documentation. The participants of this study were guidance and counseling teachers and several students at the school. The results show that guidance and counseling services are implemented through several programs, including orientation services, information services, individual counseling, group counseling, consultation, and mediation. These services aim to help students understand their potential, increase learning motivation, and develop social and emotional skills. The findings also reveal that students experience several problems such as difficulties in understanding learning materials, low learning motivation, lack of self-confidence, and conflicts with peers. Therefore, the role of guidance and counseling teachers is very important in providing guidance and support so that students are able to overcome their problems and develop optimally.